Aspek Hukum Pengadaan Barang dan Jasa Pemerintah - Mulyani, Yossy (Prosiding, 2024)
Procurement of goods and services is an activity carried out by Ministries/Institutions/Regional Apparatus which is financed by the APBN/APBD. Implementation of government procurement of goods and services must ensure the creation of legal certainty and provide protection to citizens from a series of arbitrary acts of procurement of goods and services, authority In the implementation of goods and services procurement activities, many irregularities occur, such as criminal acts of corruption. This problem poses a legal threat to Procurement Officials, Users of goods and services as well as Providers of goods and services, both from the budget planning process to planning preparation for procurement of government goods and services, to the process of handing over payments, supervision and accountability. Deviations that occur in the procurement of government goods and services have the potential to harm state finances and give rise to legal uncertainty in the application of sanctions options, whether criminal sanctions, administrative sanctions as well as demands for compensation or civil lawsuits in accordance with applicable legal regulations. There are four legal aspects in the procurement of goods and services, namely State Administration Legal Aspects, Civil Law Aspects, Criminal Law Aspects and Business Competition Legal Aspects. In order to avoid irregularities, during the process of procuring goods and services the government must apply the principles of good governance and apply the principles of procurement of goods and services such as Efficient, Effective, Open and Competitive, Transparent, Fair or non-discriminatory and Accountable